Reliability and validity of the interRAI Check-Up Self-Reported (CUSR) Assessment - Hongsoo Kim; Young-il Jung; Seungyeon Chun (BMC Geriatrics)
Abstract Background As the global population ages, the need for community-based tools to assess the functional status and care needs of older adults is increasing. This study examined the reliability, validity, and feasibility of the interRAI Check-Up Self-Reported (CUSR) in a low-income urban district in Seoul, South Korea. Methods A total of 158 older adults participated in this study. The interRAI CUSR was administered by trained lay interviewers, and psychometric testing was conducted using interrater reliability, test–retest reliability, and criterion validity measures. The study assessed the agreement between self-reported and clinician-administered assessments as well as participant feedback on feasibility and acceptability. Results The interRAI CUSR demonstrated good psychometric properties, with interrater reliability scores (mean kappa = 0.97, Gwet’s AC1 = 0.99) and test–retest reliability (mean kappa = 0.76, Gwet’s AC1 = 0.94), indicating high levels of agreement. Criterion validity showed strong correlations with the items in the interRAI Check-Up (CU) administered by clinicians. The participants reported that the tool was easy to use and accurately reflected their health status. Overall, the interRAI CUSR was found to be a reliable and feasible tool for generally healthy, pre-frail older adults residing in low-income communities. Conclusion The interRAI CUSR is a valuable tool for assessing the functional status of older adults living independently in low-income communities. By enabling self-assessment with the support of laypersons, this tool may reduce the burden on health care professionals and enhance community-based care. Further research is required to expand its applicability to diverse settings and populations.